(untitled) (Texas Journal of Philology, Culture and History, 2023)
One of the main tasks of a modern school is to prepare school graduates who can communicate freely, who understand listening and speaking in their place, who can evaluate the speech of others and, of course, their own. The article gives a detailed opinion on these issues.